Pressure to succeed in sport: An empirical analysis of the causal process that drives athletes to infringe rules - Teijón-Alcalá, Marco (Acciones e Investigaciones Sociales, 2021)
Opportunity blocking is a source of frustration historically associated with crime and other deviant behaviour. Contemporary versions of frustration theories further predict that the effects of opportunity blocking on offending are conditioned by a range of individual and social factors. This study empirically analyses the latter hypothesis in the context of sports activity/competition. More specifically, we analyse whether the influence of opportunity blocking on a series of unsporting behaviours is greater when athletes need or depend (professionally, occupationally or emotionally) on certain results. To do so, we use a sample of active athletes made up of undergraduate and postgraduate students from the Faculty of Physical Activity and Sport Sciences of the Polytechnic University of Madrid (UPM), as well as athletes who are members of sports clubs or schools in various disciplines and who compete at different levels. A series of simple moderation analyses based on the linear regression model confirm the hypothesis put forward.
Keywords: Blocking opportunities, frustration, conditioning effects, moderation analysis, rule breaking.